Manuka honey protects middle-aged rats from oxidative damage (Clinics, 2013)
OBJECTIVE: This study aimed to determine the effect of manuka honey on the oxidative status of middle-aged rats. METHOD: Twenty-four male Sprague-Dawley rats were divided into young (2 months) and middle-aged (9 months) groups. They were further divided into two groups each, which were either fed with plain water (control) or supplemented with 2.5 g/kg body weight of manuka honey for 30 days. The DNA damage level was determined via the comet assay, the plasma malondialdehyde level was determined using high performance liquid chromatography, and the antioxidant enzyme activities (superoxide dismutase, glutathione peroxidase, glutathione peroxidase and catalase) were determined spectrophotometrically in the erythrocytes and liver. The antioxidant activities were measured using 1,1-diphenyl-2-picrylhydrazyl and ferric reducing/antioxidant power assays, and the total phenolic content of the manuka was analyzed using UV spectrophotometry and the Folin-Ciocalteu method, respectively. RESULTS: Supplementation with manuka honey reduced the level of DNA damage, the malondialdehyde level and the glutathione peroxidase activity in the liver of both the young and middle-aged groups. However, the glutathione peroxidase activity was increased in the erythrocytes of middle-aged rats given manuka honey supplementation. The catalase activity was reduced in the liver and erythrocytes of both young and middle-aged rats given supplementation. Manuka honey was found to have antioxidant activity and to have a high total phenolic content. These findings showed a strong correlation between the total phenolic content and antioxidant activity. CONCLUSIONS: Manuka honey reduces oxidative damage in young and middle-aged rats; this effect could be mediated through the modulation of its antioxidant enzyme activities and its high total phenolic content. Manuka honey can be used as an alternative supplement at an early age to improve the oxidative status.